Restoring Edentulous Mandible with an Implant-Retained Overdenture in a Day by Means of Flapless Surgery and Stereolithographic Surgical Guide: a Case Report - Ilser Turkyilmaz (Stilus Optimus, 2019)
Background: Digital revolution is here and becoming more and more influential in our daily lives by transforming several things such as our habits, interactions with other people and the practice of dentistry. In implant dentistry, the newer methods by using cone-beam computed tomography and computer-aided design and computer-aided manufacturing recently offer more predictable and aesthetics outcomes in a shorter period of treatment time when compared to the traditional prosthetic procedures. Methods: A 66 year-old male patient with an edentulous mandible and several failing maxillary teeth presented to our clinic. After cone-beam computed-tomography scans and virtual implant placement by using three-dimensional software, a stereolithographic surgical guide was fabricated. The patient received two mandibular implants without any flap elevation by means of a computer-aided design and computer-aided manufacturing surgical guide and a maxillary complete denture in a day. Results: The surgical and restorative procedures were performed without any issues. The patient was followed-up for three years and no major complications with the implants and prostheses were observed. Conclusions: The technique illustrated in this report may be successfully used to restore edentulous arches in a day if it is executed by trained restorative dentists and if patient selection is appropriate.